2002
DOI: 10.1007/bf03327462
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of R-R interval variability by short-term recording in anorexia nervosa

Abstract: Subjects with anorexia nervosa (AN) present a number of changes in autonomic system functions, such as thermoregulation, vascular motility, heart rate and rhythm, and blood pressure. We evaluated the changes in the autonomic control of heart rate and blood pressure after postural variation by means of the spectral analysis of R-R interval variability (HRV in 13 female subjects with AN diagnosed on the basis of diagnostic statistical manual (DSM-IV) criteria, a mean age of 25 +/- 5.8 years and a mean body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 18 publications
3
27
2
Order By: Relevance
“…The present finding is consistent with previous results that eating disorder patients have symptoms of vagal hyperactivity [23][24][25][26]. This sympathovagal imbalance may contribute in part to cardiac autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…The present finding is consistent with previous results that eating disorder patients have symptoms of vagal hyperactivity [23][24][25][26]. This sympathovagal imbalance may contribute in part to cardiac autonomic dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…Studies on the changes in HRV following orthostatic challenge in AN patients have not produced consistent findings [27,2,36,28,32]. The time and frequency domain analysis in seated subjects showed no significant differences between the control and AN group in agreement with some previous studies [26,24,37].…”
Section: Hrv Measuressupporting
confidence: 78%
“…However other studies report no difference in LF power [39]. Increased low frequency activity [21,23,28,32,6,40,7] and an unaltered HRV [41] or very similar HRV results with a decrease in LF have also been observed [42,27]. ECG recording and analysis from a sitting patient is not uncommon and has been shown not to influence HRV analysis significantly but may result in a lower parasympathetic amplitude response and higher sympathetic response [43,44].…”
Section: Hrv Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishizawa et al (2008) reported that 32 AN patients had reduced sympathetic responsiveness and increased parasympathetic responsiveness compared with 37 healthy controls following a period of rest in the supine position. HRV appears to be abnormal in AN patients compared with healthy controls (Kriepe et al, 1994;Petretta et al, 1997;Casu et al, 2002;Melanson et al, 2004).…”
Section: Electrical and Structural Cardiac Abnormalities In Anmentioning
confidence: 99%